PEMODELAN KADAR AIR PADA SIFAT FISIK STABILISASI TANAH GAMBUT - Pradana, Mohammad Syaiful; Rohmah, Awawin Mustana (Journal of Mathematics and Mathematics Education, 2018)
Abstract: Peat soil is an organic soil with very low carrying capacity and high compressibility. The condition is less profitable for civil engineers in building a civil foundation foundation. One method of peat soil improvement can be done with astabilization method that more environment-friendly and cheaper than other methods. Laboratory based peat stabilization studies to increase carrying capacity, reduce compression and improve peat soil physical properties have been conducted in Indonesia. The results of laboratory studies shown in the graph are still limited by time and content of the mixture. Therefore, further research is needed on the mathematical model toward the physical properties of peat soil stabilization. In this research will be formulated mathematical model of water content on the physical properties of peat soil stabilization. The model is derived from the fluid equation through porous media based on the principle of continum and controlvolume. The model is then resolved numerically by different method until MacCormack scheme with two steps are predictor step using forward difference and correctorstep using backward difference. The MacCormack scheme has the advantage of solving fluid flow equations and continuity. The model is then simulated and validated by comparing the simulation results with the real system. From the simulation results obtained the water content gradually decreased, the decrease is almost close to zero. In addition, it can be seen the difference in decrease in moisture content at each test point although in small quantities.Keywords:Moisture Content, MacCormack, Peat Soil Stabilization.